Importance of Security Policy in Planning and Implementing Measures of Prevention in the Security Field (Kriminalističke teme, 2004)
Big movements and presence of transnational security challenges with multidimensional forms of endangerment in different spheres and great difficulties in their prevention, demands from adequate security organs efficient criminalistic and professional service, in intent to retain necessary level ofcomunity safety. In that context, security policy in consistent way and reliaing on the results of researches of security science and other scientific disciplines, shapes global contents for professional operationalization of different measures and goals, using established under-systems which are part of a security system in the. society. Therefore, they have to understand problems of the contemporary social reality. So, having this in mind, in this work we will elaborate the significance of the security policy, especially in shopping and implementing measures of prevention in the security field. It will be pointed at the concept of the security policy which needs to insure harmonious activity of various government agencies, and using operative mid other activities for forming suppositions for democratic and security space, said differently prevention of deviant behaviours, which burden the contemporary security reality. Accent will be. put on the specific position of the security policy in the society, because it represents one of the most important security ligature which contributes to the democratic development in all the speres of the. socilal life.